In-vivo treatment accuracy analysis of active motion-compensated liver SBRT through registration of plan dose to post-therapeutic MRI-morphologic alterations - Boda-Heggemann, Judit; Jahnke, Anika; Attenberger, Ulrike; Wenz, Frederik (Radiotherapy and oncology, 2019)
Background/purpose - In-vivo-accuracy analysis (IVA) of dose-delivery with active motion-management (gating/tracking) was performed based on registration of post-radiotherapeutic MRI-morphologic-alterations (MMA) to the corresponding dose-distributions of gantry-based/robotic SBRT-plans. - Methods - Forty targets in two patient cohorts were evaluated: (1) gantry-based SBRT (deep-inspiratory breath-hold-gating; GS) and (2) robotic SBRT (online fiducial-tracking; RS). The planning-CT was deformably registered to the first post-treatment contrast-enhanced T1-weighted MRI. An isodose-structure cropped to the liver (ISL) and corresponding to the contoured MMA was created. Structure and statistical analysis regarding volumes, surface-distance, conformity metrics and center-of-mass-differences (CoMD) was performed. - Results - Liver volume-reduction was −43.1±148.2cc post-RS and −55.8±174.3cc post-GS. The mean surface-distance between MMA and ISL was 2.3±0.8mm (RS) and 2.8±1.1mm (GS). ISL and MMA volumes diverged by 5.1±23.3cc (RS) and 16.5±34.1cc (GS); the median conformity index of both structures was 0.83 (RS) and 0.80 (GS). The average relative directional errors were ≤0.7mm (RS) and ≤0.3mm (GS); the median absolute 3D-CoMD was 3.8mm (RS) and 4.2mm (GS) without statistically significant differences between the two techniques. Factors influencing the IVA included GTV and PTV (p=0.041 and p=0.020). Four local relapses occurred without correlation to IVA. - Conclusions - For the first time a method for IVA was presented, which can serve as a benchmarking-tool for other treatment techniques. Both techniques have shown median deviations <5mm of planned dose and MMA. However, IVA also revealed treatments with errors ≥5mm, suggesting a necessity for patient-specific safety-margins. Nevertheless, the treatment accuracy of well-performed active motion-compensated liver SBRT seems not to be a driving factor for local treatment failure.
Gesehen am 13.05.2019